Ismail Raji' Al-Faruqi's Philosophy and Concept of Islamization and Integration of Science - Nasir, Muhammad; Putra, Rido (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2024)
This article focuses on the main concepts put forward by Ismail Raji' al-Faruqi related to the Islamization and integration of science. The method used in this research is a descriptive-analytical method with a contextualization approach. The primary data used in this research are the works of Ismail Raji' al-Faruqi. While the secondary data in this study are books, journal articles, and other websites that discuss the thoughts of Ismail Raji 'al-Faruqi. The results showed that for al-Faruqi, the Islamization of science is not only limited to adding Islamic elements to modern science but also involves a process of epistemological and methodological transformation. This is done to ensure that the science produced is under Islamic values, principles, and teachings. One important aspect in the Islamization of science according to al-Faruqi is the emphasis on a holistic perspective. Al-Faruqi explains that Islam offers a comprehensive view of reality, which includes spiritual, intellectual, and practical dimensions. The integration of science is an integral part of the Islamic vision of knowledge, which emphasizes the unity between science, religion, and morality. In addition, the integration of science in an Islamic perspective also includes the understanding that all knowledge comes from Allah SWT. Therefore, there is no separation between secular and religious knowledge in Islam. By emphasizing the importance of integrating Islamic principles with modern science, where tawhid is the philosophical foundation, al-Faruqi has paved the way for the development of relevant and progressive Islamic thought in the current era.